Europeanization of Ghanaian Names and Their Representations in Drama - Brew, Faustina; Brew-Riverson , Ebenezer Henry (Journal of English Language and Literature (ISSN: 2368-2132), 2018)
In Ghanaian culture a name could tell the story of when a person is born, how the person is born or some special event at the time of their birth. However, difficulties in pronunciation, as well as misinterpretation of local names by the then colonial masters resulted in alterations of many local names to the convenience of the British and Portuguese, resulting in evolution of some local names over the years to new pronunciations and spellings. During colonial dominance and immediate post-colonial period, some renowned Ghanaian playwrights used names that reflect this confusion and consequently imbedded in their characters, traits that depicted such misrepresentations as well as the specific roles the playwright assigned them. This paper reflects on the character names in relation to the settings in selected Ghanaian plays and how these characters reveal Ghanaian naming philosophies in the ways these characters play their roles. The focus is on, but not limited to, playwrights such as Kobina Sekyi, Ama Ata Aidoo, J.C. deGraft and F.K. Fiawoo who seem to be enduring points of reference particularly when one appreciates the reasoning that informs how they craft their characters, courtesy the curiously noteworthy names they drape them in. The discussion is preceded by deliberations on the indigenous naming, names and their significance furthering on the colonial influence and attempts to Europeanize.